2005
DOI: 10.1111/j.0886-0440.2005.200377s.x
|View full text |Cite
|
Sign up to set email alerts
|

Hemodynamic and Transesophageal Echocardiographic Analysis of Global and Regional Myocardial Functions, Before and Immediately After Coronary Artery Bypass Surgery

Abstract: In conclusion, a successful coronary revascularization provides an improvement in contractility in cases with chronic regional left ventricular dysfunction that is not related to irreversible necrosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 19 publications
0
2
2
Order By: Relevance
“…Another article revealed that the return of global LV dysfunction was slowly progressive with a mean time of 23 days. Improvement of segments can be seen within 15 minutes of discontinuation of cardiopulmonary bypass 24,25 . But in our study, we still did not observe improved regional strains shortly after grafting.…”
Section: Discussioncontrasting
confidence: 79%
See 1 more Smart Citation
“…Another article revealed that the return of global LV dysfunction was slowly progressive with a mean time of 23 days. Improvement of segments can be seen within 15 minutes of discontinuation of cardiopulmonary bypass 24,25 . But in our study, we still did not observe improved regional strains shortly after grafting.…”
Section: Discussioncontrasting
confidence: 79%
“…Improvement of segments can be seen within 15 minutes of discontinuation of cardiopulmonary bypass. 24,25 But in our study, we still did not observe improved regional strains shortly after grafting. There is no significant reduction or improvement of GLS in the third and fourth time points.…”
Section: Intraoperative Monitoring Of LV Performancecontrasting
confidence: 82%
“…In our study, the MPSI was not a predictor for functional improvement of LVEF or regional wall motion. We presumed that the prognostic effect could be counteracted by the presence of global stunning due to perioperative ischemia that occurs during CABG or following reperfusion injury after CABG [5][6][7] . We also evaluated myocardial thickness as another predictor of contractile functional recovery.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it has been reported that CPB impairs left ventricular contractility and cardiac function [ 25 , 26 ]. Herein, we showed that LIM when incorporated into the arterial line of the CPB system effectively stabilized perioperative cardiac function during CPB in the porcine model.…”
Section: Discussionmentioning
confidence: 99%